A case of COVID‐19 with pernio‐like skin lesions and increased red blood cell distribution width. Issue 2 (15th August 2022) - Minakawa, Satoko; Matsuzaki, Yasushi; Terada, Akari; Ogasawara, Shu; Nishiya, Yuki; Irie, Jin; Ishizawa, Yoshiya; Hanada, Hiroyuki; Sawamura, Daisuke
Abstract : Heparin resistance has been observed in patients with active severe COVID‐19 infection. The red blood cell distribution (RDW), a component of the complete blood count that reflects cellular volume variation, has been shown to be associated with elevated risk for morbidity and mortality in a wide range of diseases. Cutaneous manifestations, RDW, and levels of LD and D‐dimer might be useful biomarkers in triage of patients with COVID‐19.